Angiotensin I-converting enzyme inhibitory activity in milk fermented by wild-type and peptidase-deletion derivatives of Lactobacillus helveticus CNRZ32 - Kilpi, E.E.-R.; Kahala, M.M.; Steele, J.L.; Pihlanto, A.M.; Joutsjoki, V.V. (International dairy journal, 2007)
Development of molecular methods has enabled detailed studies of the proteolytic system of Lactobacillus helveticus, which has a central role in the release of bioactive peptides during the fermentation of milk. The impact of general aminopeptidase (PepN) and X-prolyl dipeptidyl aminopeptidase (PepX) activity of L. helveticus on the level of angiotensin I-converting enzyme (ACE) inhibitory activity in fermented milk was elucidated by taking advantage of peptidase-negative derivatives of L. helveticus CNRZ32. According to the results, increased level of ACE-inhibitory activity was attained in milk fermented by the peptidase-deficient mutants. The ACE-inhibitory activity determined with the PepN-deficient strain decreased towards the end of fermentation, suggesting that PepN gives rise to a provisional accumulation of ACE-inhibitory peptides before their hydrolysis to shorter peptides or free amino acids. The ACE-inhibitory activity determined with the PepX-deficient strain increased throughout the fermentation, indicating specific blocking of the further hydrolysis of ACE-inhibitory peptides.